Vitamin D and Other Risk Factors among Stroke Patients - Pokharel, BR; Kharel, G; Thapa, LJ; Rana, PVS (Kathmandu University Medical Journal, 2015)
Background Stroke is common neurological problems in Nepal. The common risk factors for stroke are age, hypertension, diabetes, dyslipidemia and atrial fibrillation. Vitamin D is an emerging risk factors for cardio-cerebrovascular disease.Objective This study is to find out Vitamin D and risk factors in stroke patient in Nepalese population.Method We reviewed the record of 281 stroke patients, admitted to Neurology ward of College of Medical Sciences, Bharatpur, Nepal from 1st January to 31st December 2013. The records were analyzed on the basis of age, sex, hypertension (HTN), body mass index (BMI), smoking habits, hemoglobin(Hb), diabetes mellitus(DM), Lipid profile, Atrial fibrillation(AF) and vascular territory with clinical and radiological evidences. The vitamin D analysis was done all stroke patients.Result Total patient were 281, with male 161 and age range from 18 - 87. Ischemic stroke was noted in 86.8% and hemorrhagic stroke was noted in 13.2% of patients. Middle cerebral artery (MCA) ischemia was noted in 51.5% of patients and anterior cerebral artery (ACA) ischemia was noted in 3% of patients. Multiple infarcts were noted in 12.90% of patients. About half of them were smoker, hypertension 47.40%, Diabetes mellitus 24.20% and 14.1% had atrial fibrillation. 174 (61.92%) of the stroke had less than sufficient Vitamin D.Conclusion The common risk factors for stroke patients like smoking, hypertension, diabetes mellitus and atrial fibrillations are present in Nepalese population. The level of vitamin D was also low in stroke patients.Kathmandu University Medical Journal Vol.13(1) 2015; 71-73